KEPASTIAN HUKUM PERIZINAN USAHA BAGI PELAKU UMKM - Puspa, Iftitah Prima; Triana Putri Zahrah; Sri Handayani (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting national economic growth. However, many MSME actors still face obstacles in obtaining business permits, which can affect the legality and sustainability of their businesses. Legal certainty in business licensing is therefore very important to provide protection and convenience for MSME actors. This study aims to analyze legal certainty in business licensing for MSMEs in Indonesia. The research method used is normative juridical with a statutory and conceptual approach. The results show that the government has made efforts to simplify business licensing through the implementation of the Online Single Submission (OSS) system. This system provides convenience, speed, and transparency in the licensing process. Nevertheless, challenges still exist, such as limited understanding of technology among MSME actors and uneven socialization. Therefore, stronger regulations and better assistance are needed to ensure legal certainty for MSMEs in obtaining business permits.